Monitoramento do câncer de próstata através da co-marcação de granulócitos e leucócitos com o aptâmero A4 e os anticorpos anti-EpCAM e anti-CD45 - Reis, Matheus (2019)
The prostate-specific antigen (PSA) is not able to differentiate indolent from aggressive cases of prostate cancer (CaP),presenting limitations in the follow-up for localized and metastatic neoplasia. The search for new markers is important to avoid unnecessary treatments and predict the course of the disease. With the discovery and development of the research of circulating tumor cells (CTCs), a new monitoring and prognostic tool could be used. This study describes an analysis using the flow cytometry of the aptamer A4 marking, PCP-specific PC3 ligand RNA oligonucleotide and the epithelial cell adhesion molecule (EpCAM) commonly present in tumor cells , for the detection of CTC in populations of granulocytes and leukocytes in peripheral blood samples. The purpose of this work is to increase accuracy in prostate cancer monitoring based on detection of CTCs by the aptamer A4, EpCAM marking and CD45 negative marking by flow cytometry in patients with CaP during or after treatment. The percentages of CD45-EpCAM+ granulocytes and A4+CD45-EpCAM+ leukocytes as well as A4 MFI in A4+CD45-EpCAM+ granulocytes were highly accurate in the diagnosis of prostate cancer. Only the percentage of CD45-EpCAM+ granulocytes had a correlation with the total PSA dosage, in an inverse relation, considering p<0.05. Each test detected CTCs in more than half of the patients, even with almost all subjects presenting controlled disease. Thus, the suggested co-marking was promising in the monitoring of CaP.